The Effect of Work Motivation and Principal Supervision on Teacher Performance SMK YPE SUMPIUH - Waryan; Siti Nur Azizah (Forum Ilmu Sosial)
This study aims to analyze the influence of work motivation and principal supervision on teacher performance at SMK YPE Sumpiuh. This study uses a quantitative method. The data used in this study is primary data obtained through questionnaires. The sample of this study is the entire teacher population of SMK YPE Sumpiuh, which totals 30 people. The sampling technique used is saturated sampling or the entire population is used as a sample member for the reason that the population is less than 100 people. The data were analyzed using multiple linear regression as well as validity, reliability, and classical assumption tests. The results of the study show that the work motivation and supervision of the principal have a positive and significant effect on teacher performance. The regression coefficient showed a value of 0.401 for work motivation and 0.930 for principal supervision. The Adjusted R Square value of 0.751 shows that these two variables are able to explain 75.1% of the variation in teacher performance, while other variables influence 24.9%. This study confirms that high work motivation and effective supervision from school principals can significantly improve teacher performance. Thus, school principals are advised to increase supervision and give appreciation to teachers' performance to encourage work morale and improve the quality of teaching in schools.